2015
DOI: 10.1080/19425120.2015.1057307
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Age‐0 Walleye Pollock during Late Summer: Environment or Ontogeny?

Abstract: Variability in the late‐summer vertical distribution of age‐0 Walleye Pollock Gadus chalcogrammus in the southeastern Bering Sea has been attributed to a range of physical and biological factors. Using acoustic data (38 and 120 kHz) collected during the 2010 Bering Aleutian Salmon International Survey (BASIS) and dedicated high‐resolution surveys (HR1 and HR2), we evaluated whether late‐summer distributions could be explained by water column properties (environment) or whether sampling was likely occurring dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…12: 20160276 age-0 pollock only in the upper water layers, we do not know whether these fish had a larger population size in early-iceretreat-years or if their vertical distribution in the water column changed. Low densities of large, lipid-rich crustacean zooplankton may be responsible for age-0 pollock foraging longer near the surface to accumulate lipids needed for winter survival [9], thereby delaying their ontogenetic vertical migration during early-ice-retreat-years [16].…”
Section: Discussionmentioning
confidence: 99%
“…12: 20160276 age-0 pollock only in the upper water layers, we do not know whether these fish had a larger population size in early-iceretreat-years or if their vertical distribution in the water column changed. Low densities of large, lipid-rich crustacean zooplankton may be responsible for age-0 pollock foraging longer near the surface to accumulate lipids needed for winter survival [9], thereby delaying their ontogenetic vertical migration during early-ice-retreat-years [16].…”
Section: Discussionmentioning
confidence: 99%
“…Age‐0 pollock are also associated with movements of the jellyfish, Chrysaora melanaster , which is a potential sheltering strategy to avoid predators such as seabirds, seals, and adult pollock (Brodeur, 1998a; Livingston, 1993). Parker‐Stetter et al (2015) found that aggregating behavior, which aids in predator refuge, played a larger role than environmental variables in the vertical distribution of age‐0 pollock; however, these findings were based on a single cold year (2010). Our findings support the importance of aggregating behavior in cold years but less so in warm years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, age‐0 pollock are also known to change their vertical distribution by altering their migration behavior in response to light, thermal gradients, prey, and predators (Bailey, 1989; Olla & Davis, 1990; Sogard & Olla, 1993, 1996a, 1996b; Schabetsberger et al, 2000). It is known that age‐0 pollock perform ontogenetic migration into deep layers of the water column within the first year of life (Parker‐Stetter et al, 2015), but there is only anecdotal evidence that age‐0 pollock adjust their vertical distribution in response to ocean temperatures. We analyzed the vertical distribution of age‐0 pollock in the EBS with respect to warm and cold stanzas and examined factors that may have influenced distributional shifts.…”
Section: Introductionmentioning
confidence: 99%
“…They also found substantial inter-annual variability depending on oceanographic changes in water column structure and mixed layer depth. The vertical distribution of age-0 walleye pollock and presumably Pacific cod may change seasonally due to the autumn breakdown of the thermocline, when pollock undergo an ontogenetic movement to deeper layers (Parker-Stetter et al 2015). Given this infor mation and also the differential catchability of jellyfish and forage species with the trawl used (e.g.…”
Section: Discussionmentioning
confidence: 99%